Description of Sarasaeschna kaoi sp. nov. in Taiwan, with notes on the proposed differentiating characters of the pyanan-group (Odonata, Aeshnidae) - Yeh, Wen-Chi; Lee, I-Lung; Wong, Kwok-Ching (Zootaxa, 2015)
Sarasaeschna kaoi sp. nov. collected from Yuli, Hualien County in eastern Taiwan, is easily distinguished from all known congeners by its male having short and straight cerci. Judging from male penile structure, it is considered to belong to the pyanan-group of species and resembles in general appearance the Chinese S. zhuae described from Fujian. The only known habitat of S. kaoi is a muddy and grassy swamp in natural evergreen forest. The diagnostic characters of the pyanan-group proposed by Karube & Yeh are also discussed.